Cultural and creative industries - Sánchez-Jofras, Jorge Francisco; Kuri-Alonso, Ingrid (Springer, 2019)
The purpose of this study is to explore the content of innovative culinary competence, through the educational model of Culinary Art School, which is based on learning-by-doing practices. A qualitative research strategy was implemented, including in-depth interviews with school directors and faculty. This chapter examines how the school has provided a space for the development of innovative culinary competence, demanding high standards from students, building a close relationship with industry professionals, and providing learning opportunities in real work scenarios. Taking into account the relationship between creativity and innovation, this gastronomy school takes advantage of its location in a very dynamic region in the border state of Baja California, Mexico. The educational model analyzed is based on hands-on experience, and at the same time culinary competence is acquired in real work scenarios. Considering the creative aspect of this industry, there is always an element of knowledge grounded in the social and cultural environment. The study was conducted in one particular school and was based on the curriculum and visions of directors and faculty. Based on an analysis of categories, the education model addresses key competencies in the culinary profession such as the development of culinary skills, creativity in culinary education, and the school as a space for the development of culinary innovation.
Education and innovation in gastronomy: a case study of culinary art school in Tijuana, Mexico
Keywords: Border; Chefs; Competence; Creative process; Sistemas